2021
DOI: 10.1088/1361-6579/ac3b3d
|View full text |Cite
|
Sign up to set email alerts
|

A supervised machine learning semantic segmentation approach for detecting artifacts in plethysmography signals from wearables

Abstract: Objective. Wearable devices equipped with plethysmography (PPG) sensors provided a low-cost, long-term solution to early diagnosis and continuous screening of heart conditions. However PPG signals collected from such devices often suffer from corruption caused by artifacts. The objective of this study is to develop an effective supervised algorithm to locate the regions of artifacts within PPG signals. Approach. We treat artifact detection as a 1D segmentation problem. We solve it via a novel combination of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…In their study, PPG quality was classified into five grades; it was found that the random forest SQI evaluation algorithm had the highest classification accuracy, with an accuracy of 74.5%. In a recent study, Guo et al (2021) detected wearable PPG artifacts with a DICE score of 0.87–0.91 through a combination of active-contour-based loss and an adapted U-Net architecture; compared to the existing general research methods, this method shows superior performance. However, to sufficiently verify the performance of the deep-learning model, verification using more abundant data is required.…”
Section: Resultsmentioning
confidence: 99%
“…In their study, PPG quality was classified into five grades; it was found that the random forest SQI evaluation algorithm had the highest classification accuracy, with an accuracy of 74.5%. In a recent study, Guo et al (2021) detected wearable PPG artifacts with a DICE score of 0.87–0.91 through a combination of active-contour-based loss and an adapted U-Net architecture; compared to the existing general research methods, this method shows superior performance. However, to sufficiently verify the performance of the deep-learning model, verification using more abundant data is required.…”
Section: Resultsmentioning
confidence: 99%
“…These algorithms can learn to identify patterns and relationships in the data that are difficult for humans to discern. For example, Machine Learning can detect subtle changes in breathing patterns that could indicate a respiratory disorder in respiratory plethysmography [9][10][11].…”
Section: Machine Learning In Plethysmographymentioning
confidence: 99%
“…2(c) . Several approaches have been proposed, including statistical analysis of pulse wave shape [ 56 ], assessing the level of perfusion through the perfusion index (the ratio of the amplitude of the pulsatile component of the PPG to its baseline) [ 56 ], assessing the similarity of successive pulse wave shapes using template matching [ 86 ] or dynamic time warping [ 87 ], and deep learning [ 88 ]. For further details of techniques, see [ 10 ].…”
Section: Ppg Signal Processingmentioning
confidence: 99%